Scalable preparation of furanosteroidal viridin, β-viridin and viridiol from Trichoderma virens - Wen Zhang; Kazu Sunami; Shuo Liu; Desita Triana; Zetryana Puteri Tachrim; Rikuto Kikuchi; Tohru Taniguchi; Kenji Monde; Tsunayoshi Takehara; Da-Yang Zhou; Takeyuki Suzuki; Yasuyuki Hashidoko; et al. (Scientific Reports)
Abstract Viridin and viridiol, along with wortmannin, metabolized by filamentous fungus Trichoderma virens, are identical furanosteroids with high-potent inhibitory activity towards phosphatidylinositol 3-kinase (PI3K) that associates the growth of tumor cells. Therefore, structure–activity relationship study (SAR) of these furanosteroids contributes to the development of novel drugs. However, rational supply methods have not been established yet. In this study, we generated an efficient method to produce both viridin and viridiol by using a unique pH regulated T. virens culture manner. Besides, we successfully obtained β-viridin (epimer of viridin) crystal and X-ray structure, of which the CAS number was registered without stereochemistry. Furthermore, applying the original method to stable isotope study, we also obtained [U-13C]-viridn and [U-13C]-viridol by using [U-13C6]-glucose as a carbon source replacing normal glucose which can be used to elucidate the biosynthesis pathway of furanosteroids.